(untitled) (Research, Society and Development, 2020)
The article presents the results of a pedagogical intervention project that aimed to raise awareness among students against digital piracy and in favor of the basic and advanced uses of open source software at the Federal Institute of North of Minas Gerais (IFNMG Campus Almenara), a public institution located in the Jequitinhonha Valley region (Brazil), which offers technical training courses in Informatics and in systems analysis and development. The intervention actions were based on the results of a diagnostic research in a quantitative, intersectional, self-applied survey format, with non-probability sampling for accessibility, which involved the application of 115 questionnaires among high school students. The diagnostic pointed so much to the difficulty of distinguishing between free and proprietary software, as well as the widespread use of pirated software. The intervention actions were based on the elaboration of posters dealing with the aspects identified as the most sensitive, and the intervention in the classroom with dialogue and debate on free software. It was concluded that actions were to arouse students’ interest and curiosity in relation to the alternative, safe and legal possibilities that free software offers.